THE INFLUENCE OF SPARE PARTS EXPENSES ON PRODUCTION COSTS WITH THE PREPARATION OF THE JIU VALLEY COAL - GIANINA BARSAN DUDUIALA; CARMEN FLOREA; ADRIAN VASILE SUCIU (Challenges of the Knowledge Society)
The activity of supply and that of exploitation of the spare parts from the composition of the equipments that realize the preparation of the Jiu Valley coal influence its production costs. In this respect, this paper deals with, during some periods of time, initially determined, the specific costs of the spare parts for the sieves, pumps and pipes, equipments, and also auxiliary equipments that are part of the endowment of the Exploitation of the Jiu Valley coal preparation. The results got can be used to rank and determine the causes which determine the high expenses of some spare parts categories as well as the possibility to reduce the production costs within E.P.C.V.J.